The business administration curricula at Universidad Icesi and the entrepreneurial competences development (2010)
In this paper the academic development done at the Center for Entrepreneurship Development at Universidad Icesi, in Cali – Colombia, to design and implement new entrepreneurial formation curricula in the undergraduate Business Management program is described. The new curricula is based upon 13 entr epreneurial competences and the stages that the entrepreneur and the project has to fulfil in addition to the development of the concept of the entrepreneurial components and the entrepreneurial Octahedron The new curricula has five required course an d provide a series of electives courses , internship and final project in entrepreneurship related areas. The basic objectives and the general content of each one of the required courses is presented. The model has also been used in the “Jóvenes con Empresa” Program, a project covering 10.000 university degree holders or students in the main three cities of the country with the support of International Development ban